THE EFFECT OF BLENDED LEARNING MODEL AND LEARNING MOTIVATION ON STUDENT LEARNING OUTCOMES AT SMK BINA PANGUDI LUHUR JAKARTA - Fadilah, Rismawati Nurul; Faslah, Roni; Rachmadania, Rizki Firdausi (Faculty of Economics and Business, Universitas Negeri Jakarta, 2021)
This study aims to determine the effect of the Blended Learning Model and Learning Motivation on Student Learning Outcomes at SMK Bina Pangudi Luhur Jakarta.. The research method used is a quantitative method. The research population was all students in class XI OTKP at SMK Bina Pangudi Luhur. The sample used in this study was 100 students with multiple linear regression techniques. Variable data X1 (Blended Learning) and X2 (Learning Motivation) are primary data using a Likert scale. While the data variable Y (Learning Outcomes) is secondary data by using test questions, namely pre-test and post-test. The data analysis technique used SPSS 25.0 with the results of the F test in the ANOVA table being Fcount (3,435)>Ftable (3.09). The T test in the analysis of this study is Tcount X1 (-1.982)>Ttable (-1.666) it can be concluded that there is a negative influence between the Blended Learning Learning Model on Learning Outcomes. Then for Tcount X2 (-1,624)<Ttable (-1.666) it can be concluded that there is a negative influence between Learning Motivation on Learning Outcomes. Based on the results of data analysis that this study has a multiple regression equation Y = 83,788 – 0.289 X1 – 0.323 X2. The coefficient of determination test (R2) is 0,66, which means that Blended Learning (X1) and Learning Motivation (X2) have an effect on Learning Outcomes (Y) of 66%.